PENGGUNAAN BAHASA KLISE DALAM IKLAN: PERSEPSI DAN EFEKTIVITAS KONSUMEN - Arizal Hamizar (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2022)
AbstractThis research aims to examine consumers' perceptions of the use of cliché language in advertising and the effectiveness of such language. The study employs a qualitative approach with a case study design, focused on respondents who have seen advertisements using cliché language. Purposive sampling technique was used to select relevant and representative respondents. The researcher conducted in-depth interviews with the respondents and observed their reactions to advertisements using cliché language. The results indicate that advertisements using cliché language tend to be more memorable to consumers. However, the effectiveness of using cliché language in advertising depends on the context of the advertisement and the suitability of the cliché language with the product being offered. Consumers' views on the use of cliché language in advertising can be influenced by psychological and social factors, such as creativity and originality of the advertisement. In this regard, it is important for marketers to pay attention to the brand image and message they wish to convey in their advertisements. Marketers can avoid the use of cliché language considered uncreative by developing more unique and original messages. The use of more creative and engaging language, such as metaphors or analogies, in advertising can enhance consumers' interest and attention to the advertisement and product.Keywords: Advertising, Cliche Language, Consumer Perceptions, Marketing Strategy. AbstrakPenelitian ini bertujuan untuk mengkaji persepsi konsumen terhadap penggunaan bahasa cliché dalam iklan serta efektivitas penggunaan bahasa tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus, yang difokuskan pada responden yang pernah melihat iklan yang menggunakan bahasa cliché. Teknik purposive sampling digunakan untuk memilih responden yang relevan dan representatif. Peneliti melakukan wawancara mendalam dengan responden dan observasi untuk mengamati bagaimana responden bereaksi terhadap iklan dengan penggunaan bahasa cliché. Hasil penelitian menunjukkan bahwa iklan yang menggunakan bahasa cliché cenderung lebih mudah diingat oleh konsumen. Namun, efektivitas penggunaan bahasa cliché dalam iklan sangat tergantung pada konteks iklan tersebut dan kesesuaian bahasa cliché dengan produk yang ditawarkan. Pandangan konsumen terhadap penggunaan bahasa cliché dalam iklan dapat dipengaruhi oleh faktor psikologis dan sosial, seperti kreativitas dan orisinalitas iklan. Dalam hal ini, penting bagi pemasar untuk memperhatikan citra merek dan pesan yang ingin disampaikan dalam iklan. Pemasar dapat menghindari penggunaan bahasa cliché yang dianggap tidak kreatif dengan mengembangkan pesan yang lebih unik dan orisinal. Penggunaan bahasa yang lebih kreatif dan menarik seperti penggunaan metafora atau analogi dalam iklan dapat meningkatkan minat dan perhatian konsumen terhadap iklan dan produk.Kata Kunci: Advertising, Bahasa Cliche, Persepsi Konsumen, Strategi Pemasaran.